2017
DOI: 10.1111/1440-1681.12853
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum osteocalcin levels with major adverse cardiovascular events: A 4.4‐year retrospective cohort study

Abstract: SummaryWe investigated whether the serum osteocalcin levels at baseline were associated with the incidence of major adverse cardiovascular events (MACE) in a populationbased retrospective cohort study of Chinese subjects. Coronary angiography was used to diagnose coronary artery disease (CAD). Survival curves were analyzed by performing log-rank tests with Kaplan-Meier figures. Multivariable Cox proportional hazards regression was performed to identify the association of serum osteocalcin levels with the incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…According to many authors, the increase in serum concentration of osteocalcin reflects the metabolic activity of osteoblasts of bone tissue, and also indicates its role in the regulation of the process of resorption, because under high levels of osteocalcin, bone resorption processes are also enhanced [22]. Therefore, it is both a general indicator of the level of bone metabolism and a possible prognostic indicator of the progression of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…According to many authors, the increase in serum concentration of osteocalcin reflects the metabolic activity of osteoblasts of bone tissue, and also indicates its role in the regulation of the process of resorption, because under high levels of osteocalcin, bone resorption processes are also enhanced [22]. Therefore, it is both a general indicator of the level of bone metabolism and a possible prognostic indicator of the progression of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that dysregulations of BMP pathway may make an impact on vascular dysfunctions, while overactive BMP signaling in FOP may play a central role in the development of hypoxia-induced pulmonary hypertension [18]. Recent studies have demonstrated serum OC level is closely associated with [19] found that lower serum OC levels were associated with a higher risk of major adverse cardiovascular events in a retrospective cohort study of Chinese subjects. A longitudinal analysis demonstrated that men with low OC levels exhibit increased allcause mortality and cardiovascular disease related mortality [20].…”
Section: Discussionmentioning
confidence: 99%
“…According to many authors, the increase of osteocalcin serum concentration can be considered as a possible prognostic indicator of disturbance of bone architecture 20,21 . Also, many studies have revealed its involvement in the processes of vascular calcification, which occur with the progression of atherosclerotic process 21,22 .…”
Section: Discussionmentioning
confidence: 99%